The Presence of Posyandu as an Approach in Improving Health Development in the Community - Andiko Nugraha Kusuma (Jurnal EduHealth, 2022)
Posyandu is a form of community-based health effort that is managed and organized from, by, for and with the community in the implementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services, especially to accelerate the reduction of maternal and infant mortality. . This research is a type of qualitative research, using descriptive method. While the notion of qualitative research can be understood as a research procedure that utilizes data and has the aim of describing and analyzing events, social dynamics, phenomena and attitudes of individual and group perceptions of something, the results of this study explain that community independence in health services is needed to improve visits to posyandu, but in general posyandu visits will decrease if posyandu is not managed properly, the management of posyandu is very dependent on the activity of health cadres and agencies that foster it, because posyandu is a form of Community Based Health Efforts (UKBM) which is managed from, by , for, and with the community, in order to empower the community and provide convenience to the community in obtaining basic health services. On the other hand, the presence of posyandu cadres acts as a health motivator, health educator and health service provider through the posyandu program. Because community empowerment is created from motivational factors to improve family and community health, the ability to identify health service needs and barriers, and understand available resources.